The introduction of bioterrorism in Malaysia: A legal approach - Abdullah, Nor Anita; Abdul Rahim, Rohani (UUM College of Law, Government and International Studies, 2012)
The deliberate use of biological agents and the emergence of infectious diseases which can produce harm to human health and give effects to the public health and security are well recognised.A few years back, an attack of biological agents would be the most unthinkable situation to happen. However, the threat of bioterrorism is real and it is growing.It continues to be a major challenge today and the possibility of bioterrorism is undeniable as it is increasingly defined globally as ‘not if, but when’.Therefore, this paper attempts to give a brief explanation on the threat of bioterrorism as to the emergence of infectious diseases and the legal history of international law on bioterrorism.The main objective of this paper is to fi nd out the need for bioterrorism law in Malaysian i.e. a legal approach.The study is a social legal research, which uses a qualitative approach.Thus, due to lack of materials and publications in Malaysia, in order to achieve the objectives, the methodology used was based on a semi structured interviews conducted with three respected experts in public health and security to explore the real situation in Malaysia.The authors found out that the fi nding of this study had established that an outbreak of infectious diseases can now be viewed as a threat that may result to bioterrorism if there is no preparation to handle it.